The Effect of Mitomycin C on Platelet Aggregation and Adenosine 3′, 5′-Monophosphate Metabolism - Hashimoto, Shuichi; Shibata, Sachiko; Kobayashi, Bonro (Thrombosis and Haemostasis, 1978)
The effect of Mitomycin C on aggregation, adenosine 3′, 5′-monophosphate (cyclic AMP) metabolism and reactions induced by thrombin was studied in rabbit platelets. Mitomycin C inhibited the platelet aggregation induced by adenosine diphosphate or thrombin. The level of radioactive cyclic AMP derived from 8-14C adenine or 8-14C adenosine increased after incubating intact platelets with Mitomycin G. Formation of radioactive adenosine triphosphate also increased though mitochondrial oxidation was not stimulated. Similar effect was observed also in rabbit liver. Mitomycin C failed to stimulate platelet adenyl cyclase but inhibited cyclic AMP phosphodiesterase in the absence of theophylline. In the platelets preincubated with Mitomycin C, thrombin-induced inhibition of adenyl cyclase, stimulation of membrane-bound cyclic AMP phosphodiesterase, and release of 250,000 dalton protein from platelet membranes were prevented. These results suggest that Mitomycin C will affect cellular membrane structure and function, and this extranuclear effect of Mitomycin C will lead to inhibition of aggregation in blood platelets.